Building Self-Confidence in Shy Children through Group Activities in Class A2 of RA Masjid Al Akbar Surabaya (A Case Study) - Amaliah Syafitri; Ilun Muallifah (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Low self-confidence in early childhood is reflected in doubts about personal abilities, lack of optimism, and difficulties in social interaction. This condition affects children’s ability to adapt and actively participate in learning activities. To help children overcome these challenges, role-playing activities and group activities were implemented and designed to foster children’s courage and independence. Teachers play a role as facilitators who guide and provide supporting facilities so that activities run in an enjoyable and meaningful manner. The strategies applied include the provision of play media, the arrangement of implementation time, and the provision of appreciation in each learning session.This study employed a qualitative descriptive method with a case study approach. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of group activities is able to increase the self-confidence of shy children, as children are given opportunities to interact, cooperate, and confidently express themselves within a safe and supportive social environment.